Efforts to Improve Student Learning Outcomes Using Phet Simulation Media Science Discussion Method Primary School - Ruwaida, Mediana; Dewi, Mustika Sari; Labibah, Hikmah; Shaputra, Anis (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2024)
This research discusses efforts to improve student learning outcomes in using Phet Simulation Science media through discussion methods in elementary schools. This research will reveal the learning outcomes of students at UPTD SDN 1 Keraton from the use of Phet media for series and parallel electrical circuits. An electrical circuit is a collection of electrical elements or components that are connected to each other in a certain way and generally have one closed path. A series circuit is an arrangement of electrical components connected sequentially, allowing all components in the circuit to operate with electric current. In contrast, a parallel circuit consists of electrical components arranged in branches connected in series, with the same potential but different currents flowing through each branch. The aim of this research is to find out how to deal with the discussion method in a conducive manner using Phet simulation media, and also to try to improve student learning outcomes in using Phet simulation through discussion methods in the classroom in elementary schools.